Implementation of the Eazy Passport Service Policy in Improving the Quality of Passport Issuance Services - Briandito, Fadil; Fassya, Firly Nathania (Lead Journal of Economy and Administration, 2025)
This study evaluates the Eazy Passport policy as a mobile, collective application innovation that reorients Indonesian immigration services from a government centred to a citizen centred model to expand equitable access during and after the COVID-19 period. Using a systematic literature review of policy documents, operational circulars, and field reports from 2020 - 2025, the analysis employs the SERVQUAL framework to synthesise evidence across tangibility, reliability, responsiveness, assurance, and empathy in community based delivery contexts. Findings indicate consistent gains in tangibility, responsiveness, assurance, and empathy enabled by on site biometric capture, transparent SOPs, and proximity to applicant communities which reduce office queues, lower travel costs, and target a four working day turnaround after payment. Reliability gaps persist where ICT connectivity is unstable and applicant document readiness is uneven, producing variability in completion times and occasional rework at service points. The study recommends standardising a minimum facility package for all mobile units, building connectivity redundancy and offline contingencies, providing concise pre service education (checklists and micro videos) tailored to vulnerable groups, and upskilling staff in technical and communication competencies to close residual quality gaps. Overall, Eazy Passport demonstrates measurable service quality improvements aligned with public service reform goals, with further scalability contingent on targeted infrastructure and capability strengthening across diverse locales.